PENERAPAN DISIPLIN PESERTA DIDIK MELALUI KEGIATAN SHALAT DHUHA DI MTS AL-HIDAYAH WAJAK - Muhammad Jefri; Khoirul Asfiyak; Siti Masruchah (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study aims to determine the efforts to apply student discipline through dhuha prayer activities and the supporting and inhibiting factors for implementing student discipline through dhuha prayer activities at Mts Al-Hidayah Wajak. This researcher uses qualitative research, with the type of case study. The method used in this research is observation, documentation and interviews. The technical analysis uses a data analysis model, the steps taken are data reduction, data presentation and conclusion drawing. Efforts to apply student discipline through dhuha prayer activities can be seen from the linkage of the school's vision, mission and goals, making attendance for late student dhuha prayers, making the schedule for the dhuha prayer officer, scheduling the dhuha prayer priest, the last one reading the waqiah letter before carrying outDuha prayer.supporting and inhibiting factors, including support from the school, high awareness and enthusiasm in students, adequate infrastructure. inhibiting factors in the application of student discipline through the dhuha prayer, the lack of discipline of the orderly officers who permit without prior notification and the large number of student delays, so that the implementation of the dhuha prayer is less than optimal